Internalization of Da'wah Values in the Implementation of the Independent Curriculum at MTsN 8 Ngawi. - Rizal Arfan Mah’ruf; Hafidz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was motivated by the decline in da'wah values among students. Therefore, it is necessary to internalize the values of da'wah in the world of education so that the aim of education is not only to provide provisions for general knowledge, but also religious provisions. This research aims to (1) describe what da'wah values can be internalized at MTsN 8 Ngawi in accordance with the independent curriculum and also (2) identify the stages of implementing the internalization of these da'wah values. The results of this research are (1) these values include divine values and human values. (2) the internalization stage is carried out by planning, organizing, implementing and controlling.